Epoxy coffee table from sindora spp. / Muhammad Noor Sadiman - Sadiman, Muhammad Noor (Faculty of Applied Sciences, 2019)
This final year project aims to produce Epoxy Coffee table that utilizes a combination of materials namely, wood and metal. The purpose of this project is to design an epoxy coffee table made from timber waste with an aesthetic value and to produce an Epoxy Coffee Table from Sindora spp. The top of the epoxy table was constructed with two types of materials timber waste and epoxy resin. While, the leg structure was made from metal. After the design and manufacturing process, a survey was undertaken in evaluating customer satisfaction on the characteristics of the product. A set of questionnaire was distributed to 199 respondents of different gender, age and profession. The characteristics evaluated by the respondents include material, epoxy resin, attractive, aesthetic, commercialization and price. Statistical analysia of F value for Epoxy Coffee Table from Sindora spp. shows there are no significant different for all characteristic (p>O.05) except gender for material used, epoxy resin, aesthetic and commercialize (p<O.05).